2005
DOI: 10.2320/matertrans.46.1348
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Pressure Measurements for Metal Chloride Systems by the Knudsen Effusion Method

Abstract: Thermodynamic knowledge of metal chlorides, such as vapor pressure and activity in salt/slag, are of remarkable industrial interest, particularly in fields related to the recovery/recycle/reuse of metal materials. In this study, a new apparatus for measuring the vapor pressure of metal chlorides from molten salt/slag was designed and tested with reference compounds. The results are in a good agreement with the available literature data. Using the developed apparatus, vapor pressure measurements for a KCl-NaCl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It is understandable that Cl and Zn could be evaporated in the form of CaCl 2 and metallic Zn during firing under the reducing atmosphere. 24 That is why excess CaCl 2 and ZnO are added in the reactant as preparation of chlorosilicates and sorosilicate phosphors. [11][12][13][14][15][16][17][18]25 Kang reported that the increase of the mole ratio of Cl/Ca is beneficial to crystallinity and phase purity, resulting in the enhancement luminescence intensity of Ca 8 Mg͑SiO 4 ͒ 4 Cl 2 :Eu 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…It is understandable that Cl and Zn could be evaporated in the form of CaCl 2 and metallic Zn during firing under the reducing atmosphere. 24 That is why excess CaCl 2 and ZnO are added in the reactant as preparation of chlorosilicates and sorosilicate phosphors. [11][12][13][14][15][16][17][18]25 Kang reported that the increase of the mole ratio of Cl/Ca is beneficial to crystallinity and phase purity, resulting in the enhancement luminescence intensity of Ca 8 Mg͑SiO 4 ͒ 4 Cl 2 :Eu 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…33 Therefore, the unit activity coefficient has been chosen for the model input. A similar assumption has been applied for the use of CaCl 2 (2KAlSi 3 O 8 + CaCl 2 → CaAl 2 Si 2 O 8 + 4SiO 2 + 2KCl) since there is no experimental activity coefficient available for the whole mix system except for the CaCl 2 −KCl system 34 solely and Anorthite-K-feldspar system solely. 35 This assumption for both systems discussed is then assessed by validating the model against the current experimental investigation.…”
Section: Thermodynamic Analysis Based Onmentioning
confidence: 99%
“…The FactSage calculation also suggests much lower vapor pressure (~30 times lower) compared to the experimental values. However, experimental work [84,85] suggests that the vapor pressures of molten NaCl and KCl at ~100°C above melting point 54 order of magnitude compared to ~0.15 kPa for the baseline salt at ~100°C above melting point. Therefore, the calculation above serves the purpose of showing that the experimentally measured vapor pressure reflects known physics and can be reliable.…”
mentioning
confidence: 99%